Analysis of the Suitability of Implementing Project Based Learning for Elementary School Teacher in Salatiga - Septian Airlanda, Gamaliel; Yari Dwikurnaningsih; Agustina Tyas Asri Hardini (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
Project Based Learning (PjBL) has been successfully identified as an effective learning model in the 21st century. This model has become popular among elementary school teachers. However, there are doubts about the suitability of implementing learning activities using PjBL. The ideal PjBL standard becomes too high for elementary school students. Therefore, the aim of this research is to do academic supervision steps that are able to prove these doubts. Quantitative descriptive is the type of research taken to obtain data. The research subjects were taken from four public and private schools in Salatiga City. Research data is divided into three components, therefore: the basic understanding of PjBL, suitability of model implementation, and self-reflection after implementation. It was concluded that the implementation of learning using the PjBL model by elementary school teachers was not appropriate. The research results suggest follow-up action in the form of action research to improve the abilities of elementary school teachers.